A novel microcoring technology: A completely new concept of enlarged pore treatment - Yi, Kyu‐Ho; Bae, Hyungkyu; Kim, Sung‐Yeon; Park, Hyun‐Jun; Yoon, Jeung‐Hyun; Cho, Hyun‐Jin; Kim, Hee‐Jin (Journal of cosmetic dermatology, 2023)
Background Enlarged facial pores are a common dermatological and cosmetic concern, which are difficult to treat because their pathogenesis is multifactorial. Many technological treatments have been developed to treat enlarged pores. Despite these efforts, enlarged pores remain problematic for many patients. Objectives Microcoring technology has recently been developed to treat pores and serve as a leading primary treatment option to address these concerns. Methods Three patients underwent a single treatment of rotational fractional resection. The 0.5 mm diameter rotating scalpels were used to resect the skin pores in the cheek region. The resected site was evaluated 30 days after treatment, and the patients underwent scanning in bilateral 45° views at 60 cm from the face with the same brightness setting. Results The three patients improved in terms of enlarged pores and had no severe skin‐related adverse effects. Furthermore, the three patients showed satisfactory treatment outcomes after 30 days of follow‐up. Conclusion Rotational fractional resection is a new concept that produces measurable permanent results for enlarged pore removal. These cosmetic procedures produced promising outcomes in a single treatment. However, the current clinical procedures trend demands minimally invasive treatment for enlarged pores.